What Do We Know About Balanced Scorecard and Its Benefit? A Systematic Literature Review - Blasius Erik Sibarani (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study aims to systematize articles on Balanced Scorecard (BSC) and the benefit of its adoption in various organizations and business entities. Using a systematic literature review, this study reviews 60 articles published in international reputable journals between 2003 and 2022. The articles were found using keywords such as ‘balanced scorecard’, ‘BSC’, and ‘BSC implementation’ in the Emerald, Elsevier, Sage Journals, and Scopus databases. The search was restricted by the language and scope of the research. The results show that BSC facilitates the improvement of organization performance, the achievement of organizational goals and vision, the outlining of strategies into action, the measurement of performance, the management of risk and the decision-making process.